Maciej Kruś, Akt transnarodowy w systemie europejskich aktów administracyjnych, Wydawnictwo Naukowe UAM, Poznań 2021, ss. 296, ISBN: 978-83-232-3865-2 - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2021)
Recenzja